Penerapan Model Pembelajaran Berbasis Proyek untuk Membantu Siswa Berpikir Kreatif - Emira Hayatina Ramadhan; Hindun Hindun (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
The development of the times is so fast that the role of education becomes very important in helping students to have a high skilled side. The use of project-based learning models is one way to help students think creatively. This learning model is often called project-based learning which is included in the independent curriculum. The project-based learning model is designed to facilitate the development of students' creativity skills through the application of real projects that are relevant to the learning material. This research uses a qualitative method based on literature study. The data contained in this study comes from previous studies that have been documented in the form of journals and books. The results showed that the application of project-based learning model was significantly able to improve students' creative thinking ability. Students showed improvement in the ability to formulate new ideas, solve complex problems, and collaborate effectively. In addition, they developed positive attitudes towards learning, increased motivation, and experienced improvements in the understanding of learning concepts. This research contributes to understanding the use of project-based learning model, as an effective strategy to enhance students' creativity in educational contexts. The application of the findings in this study can help educators and policy makers